Double-phase reinforced aluminum-based composite material and preparation method thereof
By adding high-entropy rare earth oxide nanoparticles and fibers to the aluminum alloy matrix and preparing composite materials by vacuum pressure impregnation method, the problem of insufficient hardness and wear resistance of the aluminum-based alloy is solved, and the high strength, hardness and thermal stability of the material are achieved.
Patent Information
- Application Number
- CN202410866456.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2025-04-25
AI Technical Summary
The existing aluminum-based alloys have low hardness and poor wear resistance, making it difficult to meet certain high-performance needs.
The composite material was prepared by adding high-entropy rare earth oxide nanoparticles and fibers to the aluminum alloy matrix using a two-phase enhancement method.
It significantly improves the strength, hardness, thermal stability and fatigue resistance of aluminum-based composite materials, enhances the high bonding strength between phase and matrix, and has excellent comprehensive performance of the material.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloys, and in particular to a dual-phase reinforced aluminum-based composite material. Background Art
[0002] Composite materials are multiphase materials formed by combining ceramic materials or polymer materials with metal materials through a certain preparation method. They usually have the material properties of different materials, can give full play to the excellent performance of different materials, have advantages that single materials cannot match, and have broad application prospects in the modern society with rapid economic and technological development. According to the classification of matrix materials, composite materials can be divided into metal-based composite materials, polymer-based composite materials and inorganic non-metal-based composite materials. Among them, metal-based composite materials have high specific strength and specific modulus, as well as good thermal and electrical conductivity, and have good applications in military industry, transportation, machinery manufacturing and other fields. Aluminum, as the most abundant metal element in the earth's crust, has the characteristics of low density, good formability and low price. It is the focus of current research and development of metal-based composite materials, mainly aimed at enhancing the shortcomings of low hardness and poor wear resistance of aluminum-based alloys. The reinforcing phase of the composite material can be divided into particles, whiskers, fibers, etc. according to their different forms. Different reinforcing phases have different reinforcing effects on the metal matrix. The fiber reinforcement phase is divided into continuous fibers and discontinuous fibers. The continuous long fibers can run through the entire metal matrix, making the composite material show various anisotropies. The discontinuous short fibers are randomly distributed in the metal matrix, making the composite material show various isotropies. The particle reinforcement phase can be divided into nanoparticles and micron particles according to their size. The addition of nanoparticles has a more prominent effect on the performance optimization of the metal matrix, and can significantly improve the wear resistance, fatigue resistance and high temperature stability of the material. The preparation methods of metal matrix composite materials include solid phase method and liquid phase method. The solid forming methods mainly include stir friction method, powder metallurgy, etc. The liquid forming methods mainly include stirring casting method, pressure infiltration method, etc. In addition, there are semi-solid stirring method, original flavor synthesis method, etc. Summary of the invention
[0003] Technical problem to be solved: The technical problem to be solved by the present invention is to provide a dual-phase reinforced aluminum-based composite material.
[0004] Technical solution: A dual-phase reinforced aluminum-based composite material comprising the following components: Aluminum alloy matrix: 81-89wt%, high entropy rare earth oxide nanoparticles: 5-9wt%, high entropy rare earth oxide fibers: 6-10wt%. Preferably, the method for preparing the dual-phase reinforced aluminum-based composite material comprises the following steps: S1. Ultrasonic dispersion: adding high entropy rare earth oxide nanoparticles and high entropy rare earth oxide fibers to deionized water for ultrasonic dispersion, and then adding a binder aluminum dihydrogen phosphate solution and stirring evenly to obtain a suspension; S2. Preform preparation: The suspension is poured into a mold, pressed and dried, and then calcined at high temperature to obtain a preform; S3. Vacuum pressure infiltration: Place the preform with the aluminum alloy at the bottom and the crucible at the top, seal and evacuate, preheat the preform, heat until the aluminum alloy is molten, then fill with argon gas and pressurize, maintain the temperature and pressure until the infiltration is completed and solidified to obtain a dual-phase reinforced aluminum-based composite material. Preferably, in step S3, the preheating temperature of the preform is 400-450°C, and the heating temperature of the aluminum alloy melt is 760-800°C. Preferably, the aluminum alloy matrix comprises the following components in weight ratio: Si: 11.2-12.5wt%, Mg: 6.5-7.5wt%, Ti: 0.2-0.4wt%, Mn: 0.1-0.3wt%, Fe: ≤0.5wt%, and the balance is Al. Preferably, the composition of the high entropy rare earth oxide nanoparticles is (La 0.15-0.25 Pr 0.15-0.25 Sm 0.15- 0.25 G 0.15-0.25 Y 0.15-0.25 )2O3, with a particle size range of 150 to 200 nm. Preferably, the preparation method of the high entropy rare earth oxide nanoparticles is a coprecipitation method, comprising the following steps: S11. Weigh each rare earth nitrate in proportion, add anhydrous ethanol and deionized water, stir and dissolve to obtain a uniform solution; S12. Ammonia water was added dropwise to the solution, and stirring was continued until the reaction was completed, and the solution was filtered to obtain a precipitate; S13. The precipitate is mixed with n-pentanol, subjected to rotary evaporation, and sintered at high temperature in an air atmosphere to obtain high-entropy rare earth oxide nanoparticles. Preferably, the sintering temperature of step S13 is 900-1100° C., and the sintering time is 3-5 hours. Preferably, the composition of the high entropy rare earth oxide fiber is (Ce 0.15-0.25 Pr 0.15-0.25 Nd 0.15- 0.25 Er 0.15-0.25 Y 0.15-0.25 )2O3, with a diameter range of 8 to 12 μm and a length of 1 to 3 mm. Preferably, the preparation method of the high entropy rare earth oxide fiber is an electrospinning method, comprising the following steps: S21. The rare earth nitrates were dissolved in a deionized water-ethanol solution in proportion, polyvinyl pyrrolidone was added and stirred to obtain a precursor solution; S22. The precursor solution is transferred into a syringe, and the process parameters are adjusted for spinning to obtain a precursor fiber; S23. Calcine the precursor fiber at high temperature in an air atmosphere to obtain high entropy rare earth oxide fiber. Preferably, the calcination temperature of step S23 is 700-900° C., and the calcination time is 1.5-2.5 h. Beneficial effects: Compared with the prior art, the present invention has the following characteristics: The aluminum-based composite material of the present invention is compositely added with high-entropy rare earth oxide nanoparticles and high-entropy rare earth oxide fibers as reinforcing phases. The nanoparticles mainly play a role in increasing strength and hardness, and the fibers mainly play a role in strengthening and toughening. The composite material has excellent mechanical properties, good thermal stability and fatigue resistance, high bonding strength between the reinforcing phase and the matrix, superior comprehensive material performance, and broad application prospects. Rare earth oxides themselves have high melting points and high thermal stability, as well as good mechanical properties. High entropy alloys have "cocktail" effect, hysteresis diffusion effect, lattice distortion effect and high entropy effect, so they have better performance than traditional materials. Extending the concept of high entropy to rare earth oxides and selecting suitable rare earth elements to prepare high entropy rare earth oxides can increase their configurational entropy and obtain a simple crystal structure, thereby obtaining excellent thermal, electrical, and mechanical properties as well as high stability and corrosion resistance. Adding nano-granular and fibrous high entropy rare earth oxides to the aluminum alloy matrix can respectively improve the hardness and toughness. At the same time, both particles and fibers as reinforcements can improve the strength of the matrix, so that the material has excellent comprehensive mechanical properties. The preparation methods of particle and short fiber reinforced metal matrix composites mainly include infiltration method and powder metallurgy method. Powder metallurgy method is a solid phase forming technology that can achieve the combination of two materials at a lower temperature, but there are many factors that affect the interface bonding, and the density of the material after forming is low, which limits its application in some fields. The vacuum pressure infiltration method is a technology that infiltrates the metal melt into the reinforcement prefabricated block under the action of external pressure to form a composite material. It is a low-cost near-net forming process, and has low requirements on the wettability between the two materials. The material interface bonding is good, which overcomes the problems of low density and poor air tightness of powder metallurgy. Therefore, the prepared composite material has good density and stable performance, and has good application prospects in the field of composite materials with light alloy as the matrix. Compared with the prior art, the present invention has the following advantages and positive effects: The present invention compositely adds nanoparticles and fibers into the aluminum alloy matrix as a reinforcing phase, the material strength and hardness are significantly improved, the thermal stability and fatigue resistance are excellent, and the material has excellent comprehensive performance. The reinforcing phases of the present invention are all high-entropy rare earth oxides, have high strength, high hardness and high stability, and have a good reinforcing effect on the metal matrix. The present invention adopts a vacuum pressure infiltration method to prepare the composite material, and the reinforcement is evenly distributed, the interface bonding is good, the material density is high and the preparation cost is low. DETAILED DESCRIPTION In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. Specific preferred examples are as follows: Embodiment 1: A dual-phase reinforced aluminum-based composite material comprising the following components: Aluminum alloy matrix: 89wt%, high entropy rare earth oxide nanoparticles: 5wt%, high entropy rare earth oxide fibers: 6wt%; the preparation method of the dual-phase reinforced aluminum-based composite material comprises the following steps: S1. Ultrasonic dispersion: adding high entropy rare earth oxide nanoparticles and high entropy rare earth oxide fibers to deionized water for ultrasonic dispersion, and then adding a binder aluminum dihydrogen phosphate solution and stirring evenly to obtain a suspension; S2. Preform preparation: The suspension is poured into a mold, pressed and dried, and then calcined at high temperature to obtain a preform; S3. Vacuum pressure infiltration: The preform is placed in a crucible with the aluminum alloy at the bottom and the preform at the top, sealed and evacuated, the preform is preheated, and then heated to melt the aluminum alloy and then filled with argon gas for pressurization, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain a dual-phase reinforced aluminum-based composite material; In step S3, the preform is preheated at 400°C and the aluminum alloy melt is heated at 760°C. The aluminum alloy matrix is composed of the following weight ratios: Si: 12.5wt%, Mg: 6.5wt%, Ti: 0.2wt%, Mn: 0.1wt%, Fe: 0.1wt%, and the balance is Al; The composition of the high entropy rare earth oxide nanoparticles is (La 0.2 Pr 0.2 Sm 0.2 G 0.2 Y 0.2 )2O3, the particle size range is 150-200nm; the preparation method of the high entropy rare earth oxide nanoparticles is a coprecipitation method, comprising the following steps: S11. Weigh each rare earth nitrate in proportion, add anhydrous ethanol and deionized water, stir and dissolve to obtain a uniform solution; S12. Ammonia water was added dropwise to the solution, and stirring was continued until the reaction was completed, and the solution was filtered to obtain a precipitate; S13. mixing the precipitate with n-pentanol, performing a rotary evaporation treatment, and sintering at a high temperature in an air atmosphere to obtain high entropy rare earth oxide nanoparticles; The sintering temperature of step S13 is 900° C. and the sintering time is 5 h; The composition of the high entropy rare earth oxide fiber is (Ce 0.2 Pr 0.2 Nd 0.2 Er 0.2 Y 0.2 )2O3, diameter ranges from 8 to 12 μm, length ranges from 1 to 3 mm; The preparation method of the high entropy rare earth oxide fiber is an electrospinning method, which comprises the following steps: S21. The rare earth nitrates were dissolved in a deionized water-ethanol solution in proportion, polyvinyl pyrrolidone was added and stirred to obtain a precursor solution; S22. The precursor solution is transferred into a syringe, and the process parameters are adjusted for spinning to obtain a precursor fiber; S23. The precursor fiber is calcined at a high temperature in an air atmosphere to obtain a high entropy rare earth oxide fiber; The calcination temperature of step S23 is 700° C. and the calcination time is 2.5 h. Embodiment 2: A dual-phase reinforced aluminum-based composite material comprising the following components: Aluminum alloy matrix: 81wt%, high entropy rare earth oxide nanoparticles: 9wt%, high entropy rare earth oxide fibers: 10wt%; the preparation method of the dual-phase reinforced aluminum-based composite material comprises the following steps: S1. Ultrasonic dispersion: adding high entropy rare earth oxide nanoparticles and high entropy rare earth oxide fibers to deionized water for ultrasonic dispersion, and then adding a binder aluminum dihydrogen phosphate solution and stirring evenly to obtain a suspension; S2. Preform preparation: The suspension is poured into a mold, pressed and dried, and then calcined at high temperature to obtain a preform; S3. Vacuum pressure infiltration: The preform is placed in a crucible with the aluminum alloy at the bottom and the preform at the top, sealed and evacuated, the preform is preheated, and then heated to melt the aluminum alloy and then filled with argon gas for pressurization, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain a dual-phase reinforced aluminum-based composite material; In step S3, the preform is preheated at 450°C and the aluminum alloy melt is heated at 800°C. The aluminum alloy matrix is composed of the following weight ratios: Si: 11.2wt%, Mg: 7.5wt%, Ti: 0.4wt%, Mn: 0.3wt%, Fe: 0.5wt%, and the balance is Al; The composition of the high entropy rare earth oxide nanoparticles is (La 0.15 Pr 0.25 Sm 0.15 G 0.25 Y 0.2 )2O3, particle size range is 150~200nm; The preparation method of the high entropy rare earth oxide nanoparticles is a coprecipitation method, comprising the following steps: S11. Weigh each rare earth nitrate in proportion, add anhydrous ethanol and deionized water, stir and dissolve to obtain a uniform solution; S12. Ammonia water was added dropwise to the solution, and stirring was continued until the reaction was completed, and the solution was filtered to obtain a precipitate; S13. mixing the precipitate with n-pentanol, performing a rotary evaporation treatment, and sintering at a high temperature in an air atmosphere to obtain high entropy rare earth oxide nanoparticles; The sintering temperature of step S13 is 1100° C. and the sintering time is 3 hours; The composition of the high entropy rare earth oxide fiber is (Ce 0.2 Pr 0.15 Nd 0.25 Er 0.15 Y 0.25 )2O3, diameter ranges from 8 to 12 μm, length ranges from 1 to 3 mm; The preparation method of the high entropy rare earth oxide fiber is an electrospinning method, which comprises the following steps: S21. The rare earth nitrates were dissolved in a deionized water-ethanol solution in proportion, polyvinyl pyrrolidone was added and stirred to obtain a precursor solution; S22. The precursor solution is transferred into a syringe, and the process parameters are adjusted for spinning to obtain a precursor fiber; S23. The precursor fiber is calcined at a high temperature in an air atmosphere to obtain a high entropy rare earth oxide fiber; The calcination temperature of step S23 is 900° C. and the calcination time is 1.5 h. Embodiment 3: A dual-phase reinforced aluminum-based composite material comprising the following components: Aluminum alloy matrix: 84wt%, high entropy rare earth oxide nanoparticles: 7wt%, high entropy rare earth oxide fibers: 9wt%; The preparation method of the dual-phase reinforced aluminum-based composite material comprises the following steps: S1. Ultrasonic dispersion: adding high entropy rare earth oxide nanoparticles and high entropy rare earth oxide fibers to deionized water for ultrasonic dispersion, and then adding a binder aluminum dihydrogen phosphate solution and stirring evenly to obtain a suspension; S2. Preform preparation: The suspension is poured into a mold, pressed and dried, and then calcined at high temperature to obtain a preform; S3. Vacuum pressure infiltration: The preform is placed in a crucible with the aluminum alloy at the bottom and the preform at the top, sealed and evacuated, the preform is preheated, and then heated to melt the aluminum alloy and then filled with argon gas for pressurization, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain a dual-phase reinforced aluminum-based composite material; In step S3, the preform is preheated at 420°C and the aluminum alloy melt is heated at 770°C; The aluminum alloy matrix is composed of the following weight ratios: Si: 11.7wt%, Mg: 7.1wt%, Ti: 0.25wt%, Mn: 0.2wt%, Fe: 0.35wt%, and the balance is Al; The composition of the high entropy rare earth oxide nanoparticles is (La 0.2 Pr 0.15 Sm 0.2 G 0.25 Y 0.2 )2O3, particle size range is 150~200nm; The preparation method of the high entropy rare earth oxide nanoparticles is a coprecipitation method, comprising the following steps: S11. Weigh each rare earth nitrate in proportion, add anhydrous ethanol and deionized water, stir and dissolve to obtain a uniform solution; S12. Ammonia water was added dropwise to the solution, and stirring was continued until the reaction was completed, and the solution was filtered to obtain a precipitate; S13. mixing the precipitate with n-pentanol, performing a rotary evaporation treatment, and sintering at a high temperature in an air atmosphere to obtain high entropy rare earth oxide nanoparticles; The sintering temperature of step S13 is 1000° C. and the sintering time is 4.5 h; The composition of the high entropy rare earth oxide fiber is (Ce 0.15 Pr 0.2 Nd 0.2 Er 0.25 Y 0.2 )2O3, diameter ranges from 8 to 12 μm, length ranges from 1 to 3 mm; The preparation method of the high entropy rare earth oxide fiber is an electrospinning method, which comprises the following steps: S21. The rare earth nitrates were dissolved in a deionized water-ethanol solution in proportion, polyvinyl pyrrolidone was added and stirred to obtain a precursor solution; S22. The precursor solution is transferred into a syringe, and the process parameters are adjusted for spinning to obtain a precursor fiber; S23. The precursor fiber is calcined at a high temperature in an air atmosphere to obtain a high entropy rare earth oxide fiber; The calcination temperature of step S23 is 750° C. and the calcination time is 2 h. Embodiment 4: A dual-phase reinforced aluminum-based composite material comprising the following components: Aluminum alloy matrix: 86wt%, high entropy rare earth oxide nanoparticles: 6wt%, high entropy rare earth oxide fibers: 8wt%; The preparation method of the dual-phase reinforced aluminum-based composite material comprises the following steps: S1. Ultrasonic dispersion: adding high entropy rare earth oxide nanoparticles and high entropy rare earth oxide fibers to deionized water for ultrasonic dispersion, and then adding a binder aluminum dihydrogen phosphate solution and stirring evenly to obtain a suspension; S2. Preform preparation: The suspension is poured into a mold, pressed and dried, and then calcined at high temperature to obtain a preform; S3. Vacuum pressure infiltration: The preform is placed in a crucible with the aluminum alloy at the bottom and the preform at the top, sealed and evacuated, the preform is preheated, and then heated to melt the aluminum alloy and then filled with argon gas for pressurization, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain a dual-phase reinforced aluminum-based composite material; In step S3, the preheating temperature of the preform is 440° C., and the heating temperature of the aluminum alloy melt is 790° C.; The aluminum alloy matrix is composed of the following weight ratios: Si: 12.2wt%, Mg: 6.8wt%, Ti: 0.3wt%, Mn: 0.15wt%, Fe: 0.4wt%, and the balance is Al; The composition of the high entropy rare earth oxide nanoparticles is (La 0.15 Pr 0.15 Sm 0.2 G 0.25 Y 0.25 )2O3, particle size range is 150~200nm; The preparation method of the high entropy rare earth oxide nanoparticles is a coprecipitation method, comprising the following steps: S11. Weigh each rare earth nitrate in proportion, add anhydrous ethanol and deionized water, stir and dissolve to obtain a uniform solution; S12. Ammonia water was added dropwise to the solution, and stirring was continued until the reaction was completed, and the solution was filtered to obtain a precipitate; S13. mixing the precipitate with n-pentanol, performing a rotary evaporation treatment, and sintering at a high temperature in an air atmosphere to obtain high entropy rare earth oxide nanoparticles; The sintering temperature of step S13 is 1050° C. and the sintering time is 3.5 h; The composition of the high entropy rare earth oxide fiber is (Ce 0.15 Pr 0.15 Nd 0.2 Er 0.25 Y 0.25 )2O3, diameter ranges from 8 to 12 μm, length ranges from 1 to 3 mm; The preparation method of the high entropy rare earth oxide fiber is an electrospinning method, which comprises the following steps: S21. The rare earth nitrates were dissolved in a deionized water-ethanol solution in proportion, polyvinyl pyrrolidone was added and stirred to obtain a precursor solution; S22. The precursor solution is transferred into a syringe, and the process parameters are adjusted for spinning to obtain a precursor fiber; S23. The precursor fiber is calcined at a high temperature in an air atmosphere to obtain a high entropy rare earth oxide fiber; The calcination temperature of step S23 is 850° C. and the calcination time is 1.5 h. Embodiment 5: A dual-phase reinforced aluminum-based composite material comprising the following components: Aluminum alloy matrix: 85wt%, high entropy rare earth oxide nanoparticles: 8wt%, high entropy rare earth oxide fibers: 7wt%; The preparation method of the dual-phase reinforced aluminum-based composite material comprises the following steps: S1. Ultrasonic dispersion: adding high entropy rare earth oxide nanoparticles and high entropy rare earth oxide fibers to deionized water for ultrasonic dispersion, and then adding a binder aluminum dihydrogen phosphate solution and stirring evenly to obtain a suspension; S2. Preform preparation: The suspension is poured into a mold, pressed and dried, and then calcined at high temperature to obtain a preform; S3. Vacuum pressure infiltration: The preform is placed in a crucible with the aluminum alloy at the bottom and the preform at the top, sealed and evacuated, the preform is preheated, and then heated to melt the aluminum alloy and then filled with argon gas for pressurization, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain a dual-phase reinforced aluminum-based composite material; In step S3, the preform is preheated at 430°C and the aluminum alloy melt is heated at 780°C; The aluminum alloy matrix is composed of the following weight ratios: Si: 11.5wt%, Mg: 7.3wt%, Ti: 0.35wt%, Mn: 0.25wt%, Fe: 0.15wt%, and the balance is Al; The composition of the high entropy rare earth oxide nanoparticles is (La 0.25 Pr 0.25 Sm -0.2 G 0.15 Y0.15 )2O3, particle size range is 150~200nm; The preparation method of the high entropy rare earth oxide nanoparticles is a coprecipitation method, comprising the following steps: S11. Weigh each rare earth nitrate in proportion, add anhydrous ethanol and deionized water, stir and dissolve to obtain a uniform solution; S12. Ammonia water was added dropwise to the solution, and stirring was continued until the reaction was completed, and the solution was filtered to obtain a precipitate; S13. mixing the precipitate with n-pentanol, performing a rotary evaporation treatment, and sintering at a high temperature in an air atmosphere to obtain high entropy rare earth oxide nanoparticles; The sintering temperature of step S13 is 950° C. and the sintering time is 4 hours; The composition of the high entropy rare earth oxide fiber is (Ce 0.25 Pr 0.25 Nd 0.2 Er 0.15 Y 0.15 )2O3, diameter ranges from 8 to 12 μm, length ranges from 1 to 3 mm; The preparation method of the high entropy rare earth oxide fiber is an electrospinning method, which comprises the following steps: S21. The rare earth nitrates were dissolved in a deionized water-ethanol solution in proportion, polyvinyl pyrrolidone was added and stirred to obtain a precursor solution; S22. The precursor solution is transferred into a syringe, and the process parameters are adjusted for spinning to obtain a precursor fiber; S23. The precursor fiber is calcined at a high temperature in an air atmosphere to obtain a high entropy rare earth oxide fiber; The calcination temperature of step S23 is 800° C. and the calcination time is 2 h. Comparative Example 1: An aluminum-based composite material comprising the following components: Aluminum alloy matrix: 93wt%, high entropy rare earth oxide nanoparticles: 7wt%; The preparation method of the aluminum-based composite material comprises the following steps: S1. Ultrasonic dispersion: Add high entropy rare earth oxide nanoparticles to deionized water for ultrasonic dispersion, then add a binder aluminum dihydrogen phosphate solution and stir evenly to obtain a suspension; S2. Preform preparation: The suspension is poured into a mold, pressed and dried, and then calcined at high temperature to obtain a preform; S3. Vacuum pressure infiltration: The preform is placed in a crucible with the aluminum alloy at the bottom and the crucible at the top, sealed and evacuated, the preform is preheated, and then heated to melt the aluminum alloy and then filled with argon gas for pressurization, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain an aluminum-based composite material; In step S3, the preheating temperature of the preform is 410° C., and the heating temperature of the aluminum alloy melt is 780° C.; The aluminum alloy matrix is composed of the following weight ratios: Si: 12.0wt%, Mg: 7.0wt%, Ti: 0.3wt%, Mn: 0.15wt%, Fe: 0.2wt%, and the balance is Al; The composition of the high entropy rare earth oxide nanoparticles is (La 0.2 Pr 0.2 Sm 0.2 G 0.2 Y 0.2 )2O3, the particle size range is 150-200nm; the preparation method of the high entropy rare earth oxide nanoparticles is a coprecipitation method, comprising the following steps: S11. Weigh each rare earth nitrate in proportion, add anhydrous ethanol and deionized water, stir and dissolve to obtain a uniform solution; S12. Ammonia water was added dropwise to the solution, and stirring was continued until the reaction was completed, and the solution was filtered to obtain a precipitate; S13. mixing the precipitate with n-pentanol, performing a rotary evaporation treatment, and sintering at a high temperature in an air atmosphere to obtain high entropy rare earth oxide nanoparticles; The sintering temperature of step S13 is 950° C. and the sintering time is 5 hours; Comparative Example 2: An aluminum-based composite material comprising the following components: Aluminum alloy matrix: 92wt%, high entropy rare earth oxide fiber: 8wt%; The preparation method of the aluminum-based composite material comprises the following steps: S1. Ultrasonic dispersion: Add high entropy rare earth oxide fibers to deionized water for ultrasonic dispersion, then add a binder aluminum dihydrogen phosphate solution and stir evenly to obtain a suspension; S2. Preform preparation: The suspension is poured into a mold, pressed and dried, and then calcined at high temperature to obtain a preform; S3. Vacuum pressure infiltration: The preform is placed in a crucible with the aluminum alloy at the bottom and the crucible at the top, sealed and evacuated, the preform is preheated, and then heated to melt the aluminum alloy and then filled with argon gas for pressurization, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain an aluminum-based composite material; In step S3, the preform is preheated at 430°C and the aluminum alloy melt is heated at 790°C; The aluminum alloy matrix is composed of the following weight ratios: Si: 11.4wt%, Mg: 6.6wt%, Ti: 0.4wt%, Mn: 0.2wt%, Fe: 0.25wt%, and the balance is Al; The composition of the high entropy rare earth oxide fiber is (Ce 0.2 Pr0.2 Nd 0.2 Er 0.2 Y 0.2 )2O3, diameter ranges from 8 to 12 μm, length ranges from 1 to 3 mm; The preparation method of the high entropy rare earth oxide fiber is an electrospinning method, which comprises the following steps: S21. The rare earth nitrates were dissolved in a deionized water-ethanol solution in proportion, polyvinyl pyrrolidone was added and stirred to obtain a precursor solution; S22. The precursor solution is transferred into a syringe, and the process parameters are adjusted for spinning to obtain a precursor fiber; S23. The precursor fiber is calcined at a high temperature in an air atmosphere to obtain a high entropy rare earth oxide fiber; The calcination temperature of step S23 is 750° C. and the calcination time is 2.5 h. Comparative Example 3: An aluminum-based composite material comprising the following components: Aluminum alloy matrix: 89wt%, rare earth oxide nanoparticles: 5wt%, rare earth oxide fibers: 6wt%; The preparation method of the aluminum-based composite material comprises the following steps: S1. Ultrasonic dispersion: rare earth oxide nanoparticles and rare earth oxide fibers are added to deionized water for ultrasonic dispersion, and then a binder aluminum dihydrogen phosphate solution is added and stirred to obtain a suspension; S2. Preform preparation: The suspension is poured into a mold, pressed and dried, and then calcined at high temperature to obtain a preform; S3. Vacuum pressure infiltration: The preform is placed in a crucible with the aluminum alloy at the bottom and the crucible at the top, sealed and evacuated, the preform is preheated, and then heated to melt the aluminum alloy and then filled with argon gas for pressurization, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain an aluminum-based composite material; In step S3, the preform is preheated at 420°C and the aluminum alloy melt is heated at 770°C; The aluminum alloy matrix is composed of the following weight ratios: Si: 12.3wt%, Mg: 6.8wt%, Ti: 0.25wt%, Mn: 0.25wt%, Fe: 0.45wt%, and the balance is Al; The composition of the rare earth oxide nanoparticles is (La 0.5 Y 0.5 )2O3, particle size range is 150~200nm; The preparation method of the rare earth oxide nanoparticles is a coprecipitation method, comprising the following steps: S11. Weigh each rare earth nitrate in proportion, add anhydrous ethanol and deionized water, stir and dissolve to obtain a uniform solution; S12. Ammonia water was added dropwise to the solution, and stirring was continued until the reaction was completed, and the solution was filtered to obtain a precipitate; S13. mixing the precipitate with n-pentanol, performing a rotary evaporation treatment, and sintering at a high temperature in an air atmosphere to obtain rare earth oxide nanoparticles; The sintering temperature of step S13 is 1000° C. and the sintering time is 4 hours; The composition of the rare earth oxide fiber is (Ce 0.5 Er 0.5 )2O3, diameter ranges from 8 to 12 μm, length ranges from 1 to 3 mm; The preparation method of the rare earth oxide fiber is an electrostatic spinning method, which comprises the following steps: S21. The rare earth nitrates were dissolved in a deionized water-ethanol solution in proportion, polyvinyl pyrrolidone was added and stirred to obtain a precursor solution; S22. The precursor solution is transferred into a syringe, and the process parameters are adjusted for spinning to obtain a precursor fiber; S23. The precursor fiber is calcined at high temperature in an air atmosphere to obtain a rare earth oxide fiber; The calcination temperature of step S23 is 800° C. and the calcination time is 2 h. Comparative Example 4: An aluminum-based composite material comprising the following components: Aluminum alloy matrix: 95wt%, high entropy rare earth oxide nanoparticles: 2wt%, high entropy rare earth oxide fibers: 3wt%; The preparation method of the aluminum-based composite material comprises the following steps: S1. Ultrasonic dispersion: adding high entropy rare earth oxide nanoparticles and high entropy rare earth oxide fibers to deionized water for ultrasonic dispersion, and then adding a binder aluminum dihydrogen phosphate solution and stirring evenly to obtain a suspension; S2. Preform preparation: The suspension is poured into a mold, pressed and dried, and then calcined at high temperature to obtain a preform; S3. Vacuum pressure infiltration: The preform is placed in a crucible with the aluminum alloy at the bottom and the crucible at the top, sealed and evacuated, the preform is preheated, and then heated to melt the aluminum alloy and then filled with argon gas for pressurization, and the temperature and pressure are maintained until the infiltration is completed and solidified to obtain an aluminum-based composite material; In step S3, the preform is preheated at 450°C and the aluminum alloy melt is heated at 760°C. The aluminum alloy matrix is composed of the following weight ratios: Si: 11.8wt%, Mg: 7.0wt%, Ti: 0.35wt%, Mn: 0.1wt%, Fe: 0.05wt%, and the balance is Al; The composition of the high entropy rare earth oxide nanoparticles is (La 0.15 Pr0.25 Sm 0.2 G 0.15 Y 0.25 )2O3, particle size range is 150~200nm; The preparation method of the high entropy rare earth oxide nanoparticles is a coprecipitation method, comprising the following steps: S11. Weigh each rare earth nitrate in proportion, add anhydrous ethanol and deionized water, stir and dissolve to obtain a uniform solution; S12. Ammonia water was added dropwise to the solution, and stirring was continued until the reaction was completed, and the solution was filtered to obtain a precipitate; S13. mixing the precipitate with n-pentanol, performing a rotary evaporation treatment, and sintering at a high temperature in an air atmosphere to obtain high entropy rare earth oxide nanoparticles; The sintering temperature of step S13 is 1050° C. and the sintering time is 4.5 h; The composition of the high entropy rare earth oxide fiber is (Ce 0.25 Pr 0.15 Nd 0.2 Er 0.25 Y 0.15 )2O3, diameter ranges from 8 to 12 μm, length ranges from 1 to 3 mm; The preparation method of the high entropy rare earth oxide fiber is an electrospinning method, which comprises the following steps: S21. The rare earth nitrates were dissolved in a deionized water-ethanol solution in proportion, polyvinyl pyrrolidone was added and stirred to obtain a precursor solution; S22. The precursor solution is transferred into a syringe, and the process parameters are adjusted for spinning to obtain a precursor fiber; S23. The precursor fiber is calcined at a high temperature in an air atmosphere to obtain a high entropy rare earth oxide fiber; The calcination temperature of step S23 is 850° C. and the calcination time is 2 h. The mechanical properties of each embodiment and comparative example were tested, and the results are shown in the table. name Bending strength / MPa Hardness / HV Tensile strength / MPa Elongation / % Example 1 243 211 336 1.33 Example 2 301 267 377 1.55 Example 3 257 234 361 1.49 Example 4 285 225 350 1.45 Example 5 278 242 347 1.42 Comparative Example 1 196 195 286 1.05 Comparative Example 2 185 182 297 1.12 Comparative Example 3 155 170 255 0.98 Comparative Example 4 209 203 315 1.27 In summary, the hardness, strength and elongation of each embodiment of the present invention are higher than those of the control example, and have excellent comprehensive mechanical properties, indicating that both particulate and fibrous high-entropy rare earth oxides have a significant reinforcing effect on the aluminum alloy matrix and can improve the comprehensive performance of the alloy.
Claims
1. A dual-phase reinforced aluminum-based composite material, characterized in that: The aluminum-based composite material comprises the following components: Aluminum alloy matrix: 81-89wt%, high entropy rare earth oxide nanoparticles: 5-9wt%, high entropy rare earth oxide fibers: 6-10wt%.
2. The method for preparing the dual-phase reinforced aluminum-based composite material according to claim 1, characterized in that: The following steps are involved: S1. Ultrasonic dispersion: adding high entropy rare earth oxide nanoparticles and high entropy rare earth oxide fibers to deionized water for ultrasonic dispersion, and then adding a binder aluminum dihydrogen phosphate solution and stirring evenly to obtain a suspension; S2. Preform preparation: The suspension is poured into a mold, pressed and dried, and then calcined at high temperature to obtain a preform; S3. Vacuum pressure infiltration: Place the preform with the aluminum alloy at the bottom and the crucible at the top, seal and evacuate, preheat the preform, heat until the aluminum alloy is molten, then fill with argon gas and pressurize, maintain the temperature and pressure until the infiltration is completed and solidified to obtain a dual-phase reinforced aluminum-based composite material.
3. The method for preparing the dual-phase reinforced aluminum-based composite material according to claim 2, characterized in that: In step S3, the preheating temperature of the preform is 400-450°C, and the heating temperature of the aluminum alloy melt is 760-800°C.
4. The dual-phase reinforced aluminum-based composite material according to claim 1, characterized in that: The aluminum alloy matrix is composed of the following weight ratios: Si: 11.2-12.5wt%, Mg: 6.5-7.5wt%, Ti: 0.2-0.4wt%, Mn: 0.1-0.3wt%, Fe: ≤0.5wt%, and the balance is Al.
5. The dual-phase reinforced aluminum-based composite material according to claim 1, characterized in that: The composition of the high entropy rare earth oxide nanoparticles is (La 0.15-0.25 Pr 0.15-0.25 Sm 0.15-0.25 G 0.15-0.25 Y 0.15-0.25 )2O3, with a particle size range of 150 to 200 nm.
6. The dual-phase reinforced aluminum-based composite material according to claim 1, characterized in that: The preparation method of the high entropy rare earth oxide nanoparticles is a coprecipitation method, comprising the following steps: S11. Weigh each rare earth nitrate in proportion, add anhydrous ethanol and deionized water, stir and dissolve to obtain a uniform solution; S12. Ammonia water was added dropwise to the solution, and stirring was continued until the reaction was completed, and the solution was filtered to obtain a precipitate; S13. The precipitate is mixed with n-pentanol, subjected to rotary evaporation, and sintered at high temperature in an air atmosphere to obtain high-entropy rare earth oxide nanoparticles.
7. The dual-phase reinforced aluminum-based composite material according to claim 6, characterized in that: The sintering temperature of step S13 is 900-1100° C., and the sintering time is 3-5 hours.
8. The dual-phase reinforced aluminum-based composite material according to claim 1, characterized in that: The composition of the high entropy rare earth oxide fiber is (Ce 0.15-0.25 Pr 0.15-0.25 Nd 0.15-0.25 Er 0.15-0.25 Y 0.15-0.25 )2O3, with a diameter range of 8 to 12 μm and a length of 1 to 3 mm.
9. The dual-phase reinforced aluminum-based composite material according to claim 1, characterized in that: The preparation method of the high entropy rare earth oxide fiber is an electrospinning method, which comprises the following steps: S21. Dissolve each rare earth nitrate in a deionized water-ethanol solution in proportion, add polyvinyl pyrrolidone and stir well to obtain a precursor solution; S22. The precursor solution is transferred into a syringe, and the process parameters are adjusted for spinning to obtain a precursor fiber; S23. Calcine the precursor fiber at high temperature in an air atmosphere to obtain high entropy rare earth oxide fiber.
10. The dual-phase reinforced aluminum-based composite material according to claim 9, characterized in that: The calcination temperature of step S23 is 700-900° C., and the calcination time is 1.5-2.5 hours.
Citation Information
Cited By
Preparation method of SiCf / TiB / Ti2AlNb composite material with double reinforcement phases of different scales
CN121250266A